2013
DOI: 10.1063/1.4843995
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of surface waves on a semi-bounded quantum magnetized collisional plasma

Abstract: The propagation of surface waves on a semi-bounded quantum plasma in the presence of the external magnetic field and collisional effects is investigated by using quantum magnetohydrodynamics model. A general analytical expression for the dispersion relation of surface waves is obtained by considering the boundary conditions. It is shown that, in some special cases, the obtained dispersion relation reduces to the results reported in previous works. It is also indicated that the quantum, external magnetic field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…[35] in a semi-bounded quantum plasma using the specular reflection method. Such QHD model has been known to be one of the powerful models for the investigation of wave dynamics in quantum plasmas [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. It has been shown that the propagation characteristics of surface waves can be modified by the effects of quantum tunneling [37][38][39][40][41][42][43][44][45][46][47][48][49][50], the external magnetic field [40,51,52], the particle-particle collisions [40], the relativistic factor [31], the particle spins [44,48], nonlocality [42,43,45], as well as, the effects of exchange-correlation of plasma particles [41,[45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…[35] in a semi-bounded quantum plasma using the specular reflection method. Such QHD model has been known to be one of the powerful models for the investigation of wave dynamics in quantum plasmas [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. It has been shown that the propagation characteristics of surface waves can be modified by the effects of quantum tunneling [37][38][39][40][41][42][43][44][45][46][47][48][49][50], the external magnetic field [40,51,52], the particle-particle collisions [40], the relativistic factor [31], the particle spins [44,48], nonlocality [42,43,45], as well as, the effects of exchange-correlation of plasma particles [41,[45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of surface waves in plasmas and in conducting solids has been a topic o f important research over the last many years [1][2][3][4][5][6][7][8][9][10][11][12]. Surface Plasmon (SP) waves can be excited due to the collective oscillation of free electrons at the interface of plasmas of different densities or plasma -vacuum interface.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Excitation of Transverse Magnetic (TM) surface waves in magnetized spin quantum plasmas was also studied by Mohamed, and he used an approximate method to obtain dispersion relation; therefore, the importance of the spin effect is not clearly shown in his results. [25,26] Those effects were found to facilitate the propagation of surface waves. [24] The effect of an external magnetic field and collision on the propagation of surface waves in quantum plasmas was studied in our previous works.…”
Section: Introductionmentioning
confidence: 99%
“…[24] The effect of an external magnetic field and collision on the propagation of surface waves in quantum plasmas was studied in our previous works. [25,26] Those effects were found to facilitate the propagation of surface waves.…”
Section: Introductionmentioning
confidence: 99%